<meta http-equiv="refresh" content="1; url=/nojavascript/">
Skip Navigation

3.3: Simpler Form of Trigonometric Equations

Difficulty Level: At Grade Created by: CK-12
Atoms Practice
Practice Simpler Form of Trigonometric Equations
Practice Now

Sometimes things are simpler than they look. For example, trigonometric identities can sometimes be reduced to simpler forms by applying other rules. For example, can you find a way to simplify

\begin{align*}\cos^3 \theta = \frac{3\cos \theta + \cos 3\theta}{4}\end{align*}cos3θ=3cosθ+cos3θ4

Keep reading, and during this Concept you'll learn ways to break down complex trigonometric equations into simpler forms. You'll be able to apply this information to the equation above.

Watch This

In the first part of this video, you'll learn how to use trigonometric substitution to simplify equations.

James Sousa Example: Solving a Trigonometric Equation Using a Trig Substitution and Factoring


By this time in your school career you have probably seen trigonometric functions represented in many ways: ratios between the side lengths of right triangles, as functions of coordinates as one travels along the unit circle and as abstract functions with graphs. Now it is time to make use of the properties of the trigonometric functions to gain knowledge of the connections between the functions themselves. The patterns of these connections can be applied to simplify trigonometric expressions and to solve trigonometric equations.

In order to do this, look for parts of the complex trigonometric expression that might be reduced to fewer trig functions if one of the identities you already know is applied to the expression. As you apply identities, some complex trig expressions have parts that can be cancelled out, others can be reduced to fewer trig functions. Observe how this is accomplished in the examples below.

Example A

Simplify the following expression using the basic trigonometric identities: \begin{align*}\frac{1 + \tan^2 x}{\csc^2 x}\end{align*}1+tan2xcsc2x

Solution: \begin{align*}\frac{1 + \tan^2 x}{\csc^2 x}&\ldots( 1 + \tan^2 x = \sec^2 x ) \text{Pythagorean Identity} \\ \frac{\sec^2 x}{\csc^2 x} & \ldots (\sec^2 x = \frac{1}{\cos^2 x}\ \text{and}\ \csc^2 x = \frac{1}{\sin^2 x}) \text{Reciprocal Identity} \\ \frac{\frac{1}{\cos^2 x}}{\frac{1}{\sin^2 x}} &= \left (\frac{1}{\cos^2 x} \right ) \div \left (\frac{1}{\sin^2 x} \right ) \\ \left (\frac{1}{\cos^2 x} \right ) \cdot \left (\frac{\sin^2 x}{1} \right ) &= \frac{\sin^2 x}{\cos^2 x}\\ & = \tan^2 x \rightarrow \text{Quotient Identity}\end{align*}

1+tan2xcsc2xsec2xcsc2x1cos2x1sin2x(1cos2x)(sin2x1)(1+tan2x=sec2x)Pythagorean Identity(sec2x=1cos2x and csc2x=1sin2x)Reciprocal Identity=(1cos2x)÷(1sin2x)=sin2xcos2x=tan2xQuotient Identity

Example B

Simplify the following expression using the basic trigonometric identities: \begin{align*}\frac{\sin^2 x + \tan^2 x + \cos^2 x}{\sec x}\end{align*}sin2x+tan2x+cos2xsecx

Solution: \begin{align*} \frac{\sin^2 x + \tan^2 x + \cos^2 x}{\sec x} &\ldots (\sin^2 x + \cos^2 x = 1) \text{Pythagorean Identity} \\ \frac{1 + \tan^2 x}{\sec x} & \ldots (1 + \tan^2 x = \sec^2 x) \text{Pythagorean Identity} \\ \frac{\sec^2 x}{\sec x} & = \sec x\end{align*}

sin2x+tan2x+cos2xsecx1+tan2xsecxsec2xsecx(sin2x+cos2x=1)Pythagorean Identity(1+tan2x=sec2x)Pythagorean Identity=secx

Example C

Simplify the following expression using the basic trigonometric identities: \begin{align*}\cos x - \cos^3x\end{align*}cosxcos3x

Solution: \begin{align*}& \cos x - \cos^3 x \\ & \cos x (1 - \cos^2 x) \qquad \ldots \text{Factor out}\ \cos x \ \text{and}\ \sin^2 x = 1 - \cos^2 x \\ & \cos x (\sin^2 x)\end{align*}

cosxcos3xcosx(1cos2x)Factor out cosx and sin2x=1cos2xcosx(sin2x)

Guided Practice

1. Simplify \begin{align*}\tan^3(x)\csc^3(x)\end{align*}tan3(x)csc3(x)

2. Show that \begin{align*}\cot^2(x) + 1 = \csc^2(x)\end{align*}cot2(x)+1=csc2(x)

3. Simplify \begin{align*}\frac{\csc^2(x)-1}{\csc^2(x)}\end{align*}csc2(x)1csc2(x)


1. \begin{align*} \tan^3(x)\csc^3(x)\\ =\frac{\sin^3(x)}{\cos^3(x)} \times \frac{1}{\sin^3(x)}\\ =\frac{1}{\cos^3(x)}\\ =\sec^3(x) \end{align*}


2. Start with \begin{align*}\sin^2(x) + \cos^2(x) = 1\end{align*}sin2(x)+cos2(x)=1, and divide everything through by \begin{align*}\sin^2(x)\end{align*}sin2(x):

\begin{align*} \sin^2(x) + \cos^2(x) = 1\\ =\frac{\sin^2(x)}{\sin^2(x)} + \frac{\cos^2(x)}{\sin^2(x)} = \frac{1}{\sin^2(x)}\\ =1 + \cot^2(x) = \csc^2(x)\\ \end{align*}


3. \begin{align*} \frac{\csc^2(x)-1}{\csc^2(x)}\\ \end{align*}


Using \begin{align*}\cot^2(x) + 1 = \csc^2(x)\end{align*}cot2(x)+1=csc2(x) that was proven in #2, you can find the relationship: \begin{align*}\cot^2(x) = \csc^2(x)-1\end{align*}cot2(x)=csc2(x)1, you can substitute into the above expression to get:

\begin{align*} \frac{\cot^2(x)}{\csc^2(x)}\\ =\frac{\frac{\cos^2(x)}{\sin^2(x)}}{\frac{1}{\sin^2(x)}}\\ =\cos^2(x)\\ \end{align*}


Concept Problem Solution

The original problem is to simplify

\begin{align*}\cos^3 \theta = \frac{3\cos \theta + \cos 3\theta}{4}\end{align*}cos3θ=3cosθ+cos3θ4

The easiest way to start is to recognize the triple angle identity:

\begin{align*}\cos 3\theta = \cos^3 \theta - 3\sin^2 \theta \cos \theta\end{align*}cos3θ=cos3θ3sin2θcosθ

Substituting this into the original equation gives:

\begin{align*}\cos^3 \theta = \frac{3\cos \theta + (\cos^3 \theta - 3\sin^2 \theta \cos \theta)}{4}\end{align*}cos3θ=3cosθ+(cos3θ3sin2θcosθ)4

Notice that you can then multiply by four and subtract a \begin{align*}\cos^3 \theta\end{align*}cos3θ term:

\begin{align*}3 \cos^3 \theta = 3 \cos \theta - 3 \sin^2 \theta \cos \theta\end{align*}3cos3θ=3cosθ3sin2θcosθ

And finally pulling out a three and dividing:

\begin{align*}\cos^3 \theta = \cos \theta - \sin^2 \theta \cos \theta\end{align*}cos3θ=cosθsin2θcosθ

Then pulling out a \begin{align*}\cos \theta\end{align*}cosθ and dividing:

\begin{align*}\cos^2 \theta = 1 - \sin^2 \theta\end{align*}cos2θ=1sin2θ

Explore More

Simplify each trigonometric expression as much as possible.

  1. \begin{align*}\sin(x)\cot(x)\end{align*}sin(x)cot(x)
  2. \begin{align*}\cos(x)\tan(x)\end{align*}cos(x)tan(x)
  3. \begin{align*}\frac{1+\tan(x)}{1+\cot(x)}\end{align*}1+tan(x)1+cot(x)
  4. \begin{align*}\frac{1-\sin^2(x)}{1+\sin(x)}\end{align*}1sin2(x)1+sin(x)
  5. \begin{align*}\frac{\sin^2(x)}{1+\cos(x)}\end{align*}sin2(x)1+cos(x)
  6. \begin{align*}(1+\tan^2(x))(\sec^2(x))\end{align*}(1+tan2(x))(sec2(x))
  7. \begin{align*}\sin(x)(\tan(x)+\cot(x))\end{align*}sin(x)(tan(x)+cot(x))
  8. \begin{align*}\frac{\sec(x)}{\sin(x)}-\frac{\sin(x)}{\cos(x)}\end{align*}sec(x)sin(x)sin(x)cos(x)
  9. \begin{align*}\frac{\sin(x)}{\cot^2(x)}-\frac{\sin(x)}{\cos^2(x)}\end{align*}sin(x)cot2(x)sin(x)cos2(x)
  10. \begin{align*}\frac{1+\sin(x)}{\cos(x)}-\sec(x)\end{align*}
  11. \begin{align*}\frac{\sin^2(x)-\sin^4(x)}{\cos^2(x)}\end{align*}
  12. \begin{align*}\frac{\tan(x)}{\csc^2(x)}+\frac{\tan(x)}{\sec^2(x)}\end{align*}
  13. \begin{align*}\sqrt{1-cos^2(x)}\end{align*}
  14. \begin{align*}(1-\sin^2(x))(\cos(x))\end{align*}
  15. \begin{align*}(\sec^2(x)+\csc^2(x))-(\tan^2(x)+\cot^2(x))\end{align*}


Trigonometric Identity

Trigonometric Identity

A trigonometric identity is an equation that relates two or more trigonometric functions.

Image Attributions


Difficulty Level:

At Grade



Date Created:

Sep 26, 2012

Last Modified:

Feb 26, 2015
You can only attach files to Modality which belong to you
If you would like to associate files with this Modality, please make a copy first.


Please wait...
Please wait...
Image Detail
Sizes: Medium | Original

Original text